Back-exchange: a novel approach to quantifying oxygen diffusion and surface exchange in ambient atmospheres. Issue 19 (27th April 2017) - Cooper, Samuel J.; Niania, Mathew; Hoffmann, Franca; Kilner, John A.
Abstract : A novel two-step Isotopic Exchange (IE) technique has been developed to investigate the influence of oxygen containing components of ambient air (such as H2 O and CO2 ) on the effective surface exchange coefficient ( k *) of a common mixed ionic electronic conductor material. Abstract : A novel two-step Isotopic Exchange (IE) technique has been developed to investigate the influence of oxygen containing components of ambient air (such as H2 O and CO2 ) on the effective surface exchange coefficient ( k *) of a common mixed ionic electronic conductor material. The two step 'back-exchange' technique was used to introduce a tracer diffusion profile, which was subsequently measured using Time-of-Flight Secondary Ion Mass Spectrometry (ToF-SIMS). The isotopic fraction of oxygen in a dense sample as a function of distance from the surface, before and after the second exchange step, could then be used to determine the surface exchange coefficient in each atmosphere. A new analytical solution was found to the diffusion equation in a semi-infinite domain with a variable surface exchange boundary, for the special case where D * and k * are constant for all exchange steps. This solution validated the results of a numerical, Crank-Nicolson type finite-difference simulation, which was used to extract the parameters from the experimental data. When modelling electrodes, D * and k * are important input parameters, which significantly impact performance. In this study La0.6 Sr0.4 Co0.2 Fe0.8 O3− δ (LSCF6428) was investigated and it was found that the rate of exchange was increased by around 250% in ambient air compared to high purity oxygen at the same p O2 . The three experiments performed in this study were used to validate the back-exchange approach and show its utility.